The Effects of Business Accelerators on Venture Performance: Evidence from Start-Up Chile - Gonzalez-Uribe, Juanita; Leatherbee, Michael (Review of Financial Studies, 2018)
Do business accelerators affect new venture performance? We investigate this question in the context of Start-Up Chile, an ecosystem accelerator. We focus on two treatment conditions typically found in business accelerators: basic services of funding and coworking space, and additional entrepreneurship schooling. Using a regression discontinuity design, we show that schooling bundled with basic services can significantly increase new venture performance. In contrast, we find no evidence that basic services affect performance on their own. Our results are most relevant for ecosystem accelerators that attract young and early-stage businesses and suggest that entrepreneurial capital matters in new ventures. Received September 1, 2015; editorial decision July 30, 2017 by Editor Francesca Cornelli.